Facing ambiguity with action - Duin, Cate (Dialog, 2023)
An insurrection, threats to our election system, and widespread distrust have spurred a national conversation about civic engagement. Many people of faith are responding with a desire to take action. However, the path to action is often deeply ambiguous. How we choose to take action that counts. This article is a personal reflection on how political engagement can animate faith and faith can guide political engagement. It suggests constant reflection on the subtle ways we can be led into complacency or inaction when interacting with political institutions. By reflecting on these mechanisms and connecting with our faith communities, this article posits that people of faith can thoughtfully and boldly make the daily decisions that make up our civic engagement.